The crash course : an honest approach to facing the future of our economy, energy, and environment - Martenson, Chris, 1962- (John Wiley & Sons, Inc., 2023)
"Energy crises. Financial market chaos. War. Climate instability. Crop failures and food shortages. Supply chain disruptions. Covid. These hot topics are an overwhelming soup of problems and predicaments. There are more to come. How do we make sense of them and what can we do to become more resilient? The Crash Course 2.0 provides a framework for understanding how all of these things are actually interconnected and, because of this, is both explanatory and predictive. The Crash Course 2.0 condenses and covers resilient solutions for the average person in four new chapters on"--